O tempo das curvas: padrões estéticos femininos no concurso de miss Piauí 1957 - SILVA, Mariane de Sales (2021)
This research approaches themes like body, beauty, women and discourses. The beauty trajectory of Chlóris Maria Guimarães Fontenele was discussed, the Miss Piauí 1957 on her participations in beauty contests of that year. We perceived that according with the common discourse about corporal pattern in these times, the measurements of the Miss were in agreement with the common expectations of the people in relation to a beautiful woman. Through the speechs of the memoirist Rubem Freitas, of the contests photographs, of the reports conveyed in Parnaíba, Rio de Janeiro, Paraná and Recife journals about the beauty of the Miss, the beauty speech that had crystallized in 1950 decade, most known as Anos Dourados, has been identified. Voluptuousness, softness and comfort was in agreement with the nacional and internacional social-political events. Analysing Parnaíba city in Piauí state, as a scenario that moved the beauty contests, in order to be included on a exterior movement, through the indication of a Parnaíba native woman to compete for a possible international title and as the broadcasted discourses claimed for a beauty pattern not only related to the body, but also to morals and familiar matters, that can be observed through the reports and photographs.